2020
DOI: 10.1038/s41439-020-00115-9
|View full text |Cite|
|
Sign up to set email alerts
|

Prevalence of the mitochondrial 1555 A>G and 1494 C>T mutations in a community-dwelling population in Japan

Abstract: Single nucleotide polymorphisms in mitochondrial DNA, such as mitochondrial 1555 A>G (m.1555 A>G) and mitochondrial 1494 C>T (m.1494 C>T), are known to be causative mutations of nonsyndromic hearing loss following exposure to aminoglycoside antibiotics. The prevalence of the m.1555 A>G and m.1494 C>T mutations has not been reported for the general population in Japan. The purpose of this study was to investigate the prevalence of m.1555 A>G and m.1494 C>T mutations in a community-dwelli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 37 publications
2
7
0
Order By: Relevance
“…Drugs whose efficacy and safety are affected by the genotype (hereafter referred to as target drugs) are listed in Table 2 . A previous study reported that the m.1555A>G pathogenic variant of MT-RNR1 in 1.9% of Japanese hearing-impaired patients ( n = 264) diagnosed using the invader-based genetic screen test (24) , whereas another report described that 1 in 1,683 (0.06%) individuals from the Japanese general population participating in the IWAKI Health Promotion Project was found to harbor the m.1555A>G variant according to TaqMan genotyping (25) . Therefore, we searched this variant against the file of the merged individual 4.7KJPN genotype, which resulted in the recruitment of three variant carriers for the study.…”
Section: Resultsmentioning
confidence: 99%
“…Drugs whose efficacy and safety are affected by the genotype (hereafter referred to as target drugs) are listed in Table 2 . A previous study reported that the m.1555A>G pathogenic variant of MT-RNR1 in 1.9% of Japanese hearing-impaired patients ( n = 264) diagnosed using the invader-based genetic screen test (24) , whereas another report described that 1 in 1,683 (0.06%) individuals from the Japanese general population participating in the IWAKI Health Promotion Project was found to harbor the m.1555A>G variant according to TaqMan genotyping (25) . Therefore, we searched this variant against the file of the merged individual 4.7KJPN genotype, which resulted in the recruitment of three variant carriers for the study.…”
Section: Resultsmentioning
confidence: 99%
“…For instance, the m.1555A > G variant known to give rise to non-syndromic hearing impairment and aminoglycoside-induced hearing impairment was absent in our cohort despite being a well-reported variant in the literature. [42][43] It is postulated that long term management by medical professionals in the public sector may not be strongly indicated for such patients with isolated hearing impairment, and thus led to the under-representation of these patients in our cohort. Similar situations may occur for patients with other milder phenotypes of MD.…”
Section: Point Prevalence Of MD In Hong Kongmentioning
confidence: 97%
“…Two pathogenic mutations in the rRNA encoding region have been reported: m.1555A>G and m.1494C>T. 56 The mutations in the mt-RNR1 region have been associated with age-related hearing loss, aminoglycoside-induced adverse effects, and autism spectrum disorder. 57 The mutation leads to a reduction of global mitochondrial protein expression and may also be influenced by the presence of other mtDNA polymorphisms. 58 …”
Section: Mitochondrial Dna Point Mutationsmentioning
confidence: 99%